Manufacturing method of polarizing plate

The method of surface modifying a protective film and bonding it to a laminated film's surface treatment layer, followed by polarizer stacking, addresses inefficiencies in polarizing plate manufacturing, resulting in plates with excellent appearance and improved adhesion.

JP7659482B2Active Publication Date: 2025-04-09NITTO DENKO CORP
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
JP2021162315
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2021-09-30
Publication Date
2025-04-09
Estimated Expiration
2041-09-30

AI Technical Summary

Technical Problem

Existing methods for manufacturing polarizing plates are inefficient and do not consistently produce plates with excellent exterior appearance.

Method used

A method involving surface modification of a protective film with a surface roughness of 0.5 μm or less, followed by bonding the modified film to a laminated film's surface treatment layer, and then stacking a polarizer on the substrate side of the laminate.

Benefits of technology

This method enables the efficient manufacture of polarizing plates with excellent appearance by improving adhesion and reducing surface roughness, thus preventing unevenness and enhancing manufacturing efficiency.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007659482000002
    Figure 0007659482000002
  • Figure 0007659482000003
    Figure 0007659482000003
  • Figure 0007659482000004
    Figure 0007659482000004
Patent Text Reader

Abstract

To enable production of a polarizing plate which is highly efficient and has superior external appearance.SOLUTION: A method of manufacturing a polarizing plate according to an embodiment of the present invention comprises: surface-modifying a first main surface of a protective film having the first main surface and a second main surface that are facing each other, the first main surface having a surface roughness Ra of 0.5 μm or less; obtaining a laminate by bonding the surface-modified surface of the protective film to a surface-treated layer of a laminated film comprising a base material and the surface-treated layer, and laminating a polarizer on the laminate on the base material side.SELECTED DRAWING: Figure 1A
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a method for producing a polarizing plate. [Background technology]

[0002] Image display devices, such as liquid crystal display devices and electroluminescence (EL) display devices (e.g., organic EL display devices and inorganic EL display devices), are rapidly becoming widespread. In image display panels mounted on image display devices, polarizing plates are generally used. Typically, polarizing plates with retardation layers, which are formed by integrating a polarizing plate and a retardation plate, are widely used (e.g., Patent Document 1).

[0003] The polarizing plate is typically obtained by laminating a polarizer having a polarizing function with a member for protecting the polarizing plate, and it is desired to improve the efficiency of manufacturing the polarizing plate by performing this lamination well.It is also desired to manufacture a polarizing plate having excellent appearance. [Prior art documents] [Patent documents]

[0004] [Patent Document 1] Patent No. 3325560 Summary of the Invention [Problem to be solved by the invention]

[0005] In view of the above, a primary object of the present invention is to efficiently produce a polarizing plate having excellent appearance. [Means for solving the problem]

[0006] According to an embodiment of the present invention, there is provided a method for producing a polarizing plate, which includes surface-modifying a first main surface of a protective film having a first main surface and a second main surface opposed to each other, the first main surface having a surface roughness Ra of 0.5 μm or less, bonding the surface-modified surface of the protective film to the surface treatment layer of a laminate film having a substrate and a surface treatment layer to obtain a laminate, and laminating a polarizer on the substrate side of the laminate. In one embodiment, the surface modification is performed by at least one of a corona treatment or a plasma treatment. In one embodiment, the surface roughness Ra of the first main surface is reduced by 0.1 μm to 0.4 μm by the surface modification. In one embodiment, the first main surface has a surface roughness Ra of 0.15 μm or less after the surface modification. In one embodiment, the surface modification is performed by corona treatment, and the treatment intensity of the corona treatment is 10 W·min / m 2 More than 50W min / m 2 The following is the result. In one embodiment, the laminate and the polarizer are superimposed on each other, and then the laminate and the polarizer are sandwiched between a pair of pressure members and pressurized. In one embodiment, the protective film is a polyolefin film. In one embodiment, the surface treatment layer contains at least one of fluorine or silicon. In one embodiment, the reflectance of the surface treatment layer side of the laminate film is 3% or less. Effect of the Invention

[0007] According to the embodiment of the present invention, a polarizing plate having excellent appearance can be produced efficiently. [Brief description of the drawings]

[0008] [Figure 1A] FIG. 1 is a diagram showing a first manufacturing process of a polarizing plate according to one embodiment of the present invention. [Figure 1B]FIG. 2 is a diagram showing step 2 following step 1. [Figure 1C] FIG. 4 is a diagram showing step 3 following step 2. [Figure 2A] 2 is an observation photograph of the polarizing plate of Example 1. [Figure 2B] 1 is an observation photograph of a polarizing plate of Comparative Example 2. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0009] Hereinafter, the embodiments of the present invention will be described with reference to the drawings, but the present invention is not limited to these embodiments. In addition, in order to clarify the description, the width, thickness, shape, etc. of each part may be shown more diagrammatically than in the embodiment, but these are merely examples and do not limit the interpretation of the present invention.

[0010] (Definition of terms and symbols) The definitions of terms and symbols used in this specification are as follows. (1) Refractive index (nx, ny, nz) "nx" is the refractive index in the direction in which the in-plane refractive index is maximum (i.e., the slow axis direction), "ny" is the refractive index in the direction perpendicular to the slow axis in the plane (i.e., the fast axis direction), and "nz" is the refractive index in the thickness direction. (2) In-plane phase difference (Re) "Re(λ)" is the in-plane retardation measured with light of wavelength λ nm at 23° C. For example, "Re(550)" is the in-plane retardation measured with light of wavelength 550 nm at 23° C. Re(λ) is calculated by the formula: Re(λ)=(nx-ny)×d, where d(nm) is the thickness of the layer (film). (3) Retardation in the thickness direction (Rth) "Rth(λ)" is the retardation in the thickness direction measured with light of wavelength λ nm at 23° C. For example, "Rth(550)" is the retardation in the thickness direction measured with light of wavelength 550 nm at 23° C. Rth(λ) is calculated by the formula: Rth(λ)=(nx-nz)×d, where d(nm) is the thickness of the layer (film).

[0011] A method for producing a polarizing plate according to one embodiment of the present invention includes surface modifying a first main surface of a protective film having first and second main surfaces facing each other (surface modification step, step 1), bonding the surface modified surface of the protective film to the surface treatment layer of a laminate film having a substrate and a surface treatment layer to obtain a laminate (attaching step, step 2), and laminating a polarizer on the substrate side of the laminate (lamination step, step 3).

[0012] 1A to 1C are diagrams showing steps of a method for producing a polarizing plate according to one embodiment of the present invention.

[0013] In step 1 shown in Fig. 1A, a first main surface 10a of a protective film 10 having a first main surface 10a and a second main surface 10b facing each other is surface-modified. The protective film 10 is typically long and can be wound into a roll. Here, "long" refers to an elongated shape in which the length is sufficiently longer than the width, for example, 10 times or more, preferably 20 times or more, the length of the width.

[0014] In step 2, the protective film 10 with the first main surface 10a surface-modified is bonded to the surface treatment layer 22 of the laminate film 20 having the substrate 21 and the surface treatment layer 22, and FIG. 1B shows the completed state of the laminate 90. As shown in the figure, the first main surface 10a of the protective film 10 is bonded to the surface treatment layer 22. The protective film 10 and the laminate film 20 are laminated, for example, while being transported by rolls (so-called roll-to-roll). By using the surface-modified protective film, a laminate with excellent adhesion to the laminate film can be obtained. A laminate with excellent adhesion can suppress peeling of the protective film from the laminate film in a later step, which can contribute to improving manufacturing efficiency.

[0015] Typically, the surface energy of the first main surface is increased by the surface modification. The surface modification is performed, for example, by a corona treatment or a plasma treatment. These may be used alone or in combination.

[0016] Preferably, a corona treatment is employed. The corona treatment is performed, for example, by applying a high voltage at a high frequency between a dielectric and an insulated electrode to generate a corona, and then disposing a protective film between the dielectric and the electrode. The distance between the electrode and the protective film is, for example, 1.5 mm to 2.5 mm. In one embodiment, the corona treatment is performed while the protective film is being transported. Specifically, the corona treatment is performed while the long protective film is being transported in the longitudinal direction. The transport speed of the protective film is, for example, 10 m / min to 20 m / min. The electrode width (treatment width) is, for example, 1.3 m to 1.5 m. The corona output is, for example, 0.5 kW to 1.0 kW. The treatment intensity calculated from the following formula is, for example, 10 W·min / m 2 or more, preferably 15 W·min / m 2 More preferably, 20 W·min / m 2 This is all. With this treatment strength, excellent adhesion to the laminated film can be obtained. On the other hand, the treatment strength calculated from the following formula is, for example, 50 W·min / m 2 less than 45 W·min / m 2 less than 40W·min / m 2 Such a treatment intensity can suppress problems such as undulations occurring in the protective film due to the corona treatment. Treatment strength = corona output / protective film transport speed x electrode width

[0017] As the protective film, a polyolefin film is preferably used. Specifically, the protective film is preferably composed of polyethylene, polypropylene, or a mixture thereof. Here, polyethylene includes ethylene homopolymers and copolymers of ethylene and other olefins. Polypropylene includes propylene homopolymers and copolymers of propylene and other olefins.

[0018] Specific examples of the polyethylene include high density polyethylene (HDPE), low density polyethylene (LDPE), and linear low density polyethylene (L-LDPE).

[0019] Examples of the other olefins include ethylene, propylene, butene, pentene, hexene, heptene, octene, nonene, and decene. Among these, ethylene, propylene, and butene are preferably used. In preparing a copolymer of ethylene or propylene and other olefins, the blending ratio of the other olefins is preferably 40 parts by weight or less, more preferably 30 parts by weight or less, and even more preferably 20 parts by weight or less, based on 100 parts by weight of the total of ethylene or propylene and other olefins.

[0020] In one embodiment, the polyolefin film preferably contains polyethylene. Specifically, the polyolefin film is preferably a polyethylene film or a mixture film of polyethylene and polypropylene. When the polyolefin film contains a mixture of polyethylene and polypropylene, the content of polyethylene is preferably 60 parts by weight or more and 97 parts by weight or less, more preferably 70 parts by weight or more, and even more preferably 80 parts by weight or more, based on 100 parts by weight of the total of polyethylene and polypropylene.

[0021] The protective film (polyolefin film) may contain other ingredients such as particles, pigments, colorants, antistatic agents, UV absorbers, antioxidants, heat stabilizers, and chlorine scavengers.

[0022] The protective film (polyolefin film) may be a single layer having a uniform composition, or may have a laminated structure of two or more layers having different compositions. Specific examples of the laminated structure include a two-layer structure of a first layer and a second layer having different compositions, and a three-layer structure of a first layer, a second layer, and a third layer. The first layer and the third layer may have substantially the same composition or may have different compositions. The protective film (polyolefin film) may be a non-stretched film or a stretched film, but is preferably a non-stretched film.

[0023] The thickness of the protective film is, for example, 20 μm to 150 μm, preferably 30 μm to 100 μm, and more preferably 40 μm to 80 μm.

[0024] The surface roughness Ra of the first main surface of the protective film before surface modification is 0.5 μm or less, preferably 0.4 μm or less, and more preferably 0.3 μm or less. By using such a protective film, a polarizing plate with excellent appearance can be obtained. On the other hand, the surface roughness Ra of the first main surface of the protective film before surface modification is, for example, 0.2 μm or more.

[0025] By the surface modification, the surface roughness Ra of the first main surface of the protective film is preferably reduced by 0.1 μm to 0.4 μm, and more preferably by 0.15 μm to 0.25 μm.

[0026] The surface roughness Ra of the first main surface of the protective film after the surface modification is preferably 0.15 μm or less, more preferably 0.1 μm or less, and even more preferably 0.05 μm or less. On the other hand, the surface roughness Ra of the first main surface of the protective film after the surface modification treatment is, for example, 0.01 μm or more.

[0027] Although not shown, the laminate 90 may be subjected to a treatment using water before step 3 described later. Specifically, the laminate 90 may be immersed in a treatment bath containing water. In one embodiment, the substrate 21 of the laminate 90 is subjected to a chemical treatment (e.g., saponification treatment) by the treatment using water. By using a surface-modified protective film, peeling of the laminate can be suppressed even when the laminate is subjected to a treatment using water. After the treatment using water, the laminate 90 may be subjected to a drying treatment.

[0028] In step 3, the laminate 90 and the polarizer 30 are laminated together, and FIG. 1C shows the completed state of the polarizing plate 100. The substrate 21 of the laminate 90 (laminated film 20) can function as a protective layer for the polarizer. In the illustrated example, when laminating the laminate 90, a protective layer 40 is laminated on one side of the polarizer 30. The protective layer 40 may function as a retardation layer (e.g., a λ / 4 plate). The laminate 90 and the polarizer 30 (a laminate of the polarizer 30 and the protective layer 40) are laminated together, for example, while they are transported by rolls (so-called roll-to-roll method).

[0029] Preferably, from the viewpoint of ensuring the lamination of the laminate 90 and the polarizer 30, after the laminate 90 and the polarizer 30 are laminated (in the illustrated example, after the laminate 90, the polarizer 30, and the protective layer 40 are laminated), they are sandwiched between a pair of pressure members and pressurized (in the direction of the arrow in FIG. 3). The pressure condition is, for example, 0.2 MPa to 0.4 MPa. For example, rubber or metal is used as the material of the pressure member. By using a protective film that satisfies the above-mentioned predetermined surface roughness Ra, a polarizing plate with excellent appearance can be obtained. Specifically, if a protective film with a large surface roughness Ra value (for example, exceeding 0.5 μm) is used, there is a risk that unevenness will occur in the obtained polarizing plate due to the uneven shape of the protective film surface when the laminate 90 and the polarizer 30 are laminated.

[0030] Although not shown, the polarizing plate 100 may include other members. For example, it may include a retardation layer (e.g., a λ / 4 plate) arranged on the side of the polarizer 30 where the laminate film 20 is not arranged. Specifically, after laminating the laminate 90 and the polarizer 30 (a laminate of the polarizer 30 and the protective layer 40), a retardation layer may be further laminated.

[0031] The above members may be laminated via any appropriate adhesive layer. Specific examples of the adhesive layer include an adhesive layer and a pressure-sensitive adhesive layer. For example, the polarizer and the protective layer are bonded together via an adhesive layer. Specifically, the polarizer and the protective layer are bonded together using an active energy ray-curable adhesive. The thickness of the active energy ray-curable adhesive after curing (thickness of the adhesive layer) is, for example, 0.2 μm to 3.0 μm, preferably 0.4 μm to 2.0 μm, and more preferably 0.6 μm to 1.5 μm.

[0032] The protective film 10 is peelably attached to the laminate film 20. The protective film 10 may be peeled off before the polarizing plate obtained according to the embodiment of the present invention is used (for example, before it is laminated on an image display panel) or during the manufacturing process of the final product (image display device), or may be mounted directly on the final product.

[0033] [Polarizer] The polarizer is typically a resin film containing a dichroic substance (e.g., iodine). Examples of the resin film include hydrophilic polymer films such as polyvinyl alcohol (PVA) films, partially formalized PVA films, and partially saponified ethylene-vinyl acetate copolymer films.

[0034] The thickness of the polarizer is preferably 18 μm or less, more preferably 15 μm or less, and further preferably 12 μm or less, while the thickness of the polarizer is preferably 1 μm or more.

[0035] The polarizer preferably exhibits absorption dichroism at any wavelength of 380 nm to 780 nm. The single transmittance of the polarizer is, for example, 41.5% to 46.0%, preferably 42.0% to 46.0%, and more preferably 44.5% to 46.0%. The degree of polarization of the polarizer is preferably 97.0% or more, more preferably 99.0% or more, and even more preferably 99.9% or more.

[0036] The polarizer may be produced by any appropriate method. Specifically, the polarizer may be produced from a single-layer resin film or may be produced using a laminate of two or more layers.

[0037] A method for producing a polarizer from the above-mentioned single-layer resin film typically includes subjecting the resin film to a dyeing treatment with a dichroic substance such as iodine or a dichroic dye, and a stretching treatment. As the resin film, for example, a hydrophilic polymer film such as a polyvinyl alcohol (PVA) film, a partially formalized PVA film, or an ethylene-vinyl acetate copolymer partially saponified film is used. The method may further include an insolubilization treatment, a swelling treatment, a crosslinking treatment, etc. Such a production method is well known and commonly used in the art, so a detailed description thereof will be omitted.

[0038] The polarizer obtained by using the laminate can be produced, for example, by using a laminate of a resin substrate and a resin film or resin layer (typically, a PVA-based resin layer). Specifically, the laminate can be produced by applying a PVA-based resin solution to a resin substrate, drying the resin substrate to form a PVA-based resin layer on the resin substrate, and obtaining a laminate of the resin substrate and the PVA-based resin layer; and stretching and dyeing the laminate to make the PVA-based resin layer into a polarizer. In this embodiment, preferably, a PVA-based resin layer containing a halide and a PVA-based resin is formed on one side of the resin substrate. The stretching typically includes immersing the laminate in an aqueous boric acid solution and stretching it. Furthermore, the stretching may further include, as necessary, stretching the laminate in air at a high temperature (for example, 95°C or higher) before stretching in the aqueous boric acid solution. In addition, in this embodiment, preferably, the laminate is subjected to a drying shrinkage treatment in which the laminate is heated while being transported in the longitudinal direction to shrink the laminate by 2% or more in the width direction. Typically, the manufacturing method of the present embodiment includes subjecting the laminate to an air-assisted stretching treatment, a dyeing treatment, an underwater stretching treatment, and a drying shrinkage treatment in this order. By introducing the auxiliary stretching, even when PVA is applied onto a thermoplastic resin, it is possible to increase the crystallinity of PVA, and high optical properties can be achieved. In addition, by simultaneously increasing the orientation of PVA in advance, problems such as a decrease in the orientation of PVA and dissolution can be prevented when immersed in water in the subsequent dyeing and stretching steps, and high optical properties can be achieved. Furthermore, when the PVA-based resin layer is immersed in a liquid, the orientation disorder and the decrease in the orientation of the PVA molecules can be suppressed compared to when the PVA-based resin layer does not contain a halide, and high optical properties can be achieved. Furthermore, by shrinking the laminate in the width direction by the drying shrinkage treatment, high optical properties can be achieved. A polarizing plate can be obtained by laminating a protective layer on the peeled surface obtained by peeling the resin substrate from the obtained resin substrate / polarizer laminate, or on the surface opposite to the peeled surface. Details of such a method for producing a polarizer are described in, for example, JP 2012-73580 A and Japanese Patent No. 6470455. The entire disclosures of these publications are incorporated herein by reference.

[0039] [Protective layer] The protective layer may be formed of any suitable film that can be used as a protective layer for a polarizer. Specific examples of materials that are the main components of the film include cellulose-based resins such as triacetyl cellulose (TAC), polyester-based, polyvinyl alcohol-based, polycarbonate-based, polyamide-based, polyimide-based, polyethersulfone-based, polysulfone-based, polystyrene-based, cycloolefin-based such as polynorbornene, polyolefin-based, (meth)acrylic, acetate-based, and other resins.

[0040] The thickness of the protective layer is preferably 5 μm to 80 μm, more preferably 10 μm to 40 μm, and further preferably 15 μm to 35 μm.

[0041] In one embodiment, the protective layer 40 arranged on the side of the polarizer 30 where the laminate film 20 is not arranged is preferably optically isotropic. In this specification, "optically isotropic" means that the in-plane retardation Re(550) is 0 nm to 10 nm and the retardation in the thickness direction Rth(550) is -10 nm to +10 nm.

[0042] [Laminated film] The laminated film has a substrate and a surface treatment layer formed on the substrate. The substrate can function as a protective layer for the polarizer, and the details thereof are as described above. The polarizing plate obtained by the embodiment of the present invention is typically disposed on the viewing side of an image display device, and the laminated film is disposed on the viewing side. In one embodiment, the surface treatment layer of the laminated film is located on the outermost surface of the image display device. Therefore, it is preferable that the substrate (protective layer on the viewing side) is provided with a surface treatment layer such as a hard coat (HC) treatment, an anti-reflection treatment, an anti-sticking treatment, an anti-glare treatment, or an anti-fouling treatment.

[0043] In one embodiment, the surface treatment layer has an antiglare function and an antireflection function. Specifically, the surface treatment layer has an antiglare layer and an antireflection layer in this order from the substrate side. The antiglare layer typically contains a resin and a filler. Specifically, the resin contains a filler, and the surface of the resulting layer (antiglare layer) is formed with a fine uneven shape, thereby obtaining antiglare properties. By providing an antiglare layer, for example, on the surface of an image display device, external light such as fluorescent light and sunlight is scattered, image reflection is suppressed, and a decrease in contrast can be prevented. The antireflection layer can reduce reflection on the surface of the antiglare layer. The reflectance of the surface treatment layer side of the laminated film is preferably 3% or less, more preferably 1% or less.

[0044] The antireflection layer can be obtained, for example, by applying a coating liquid for forming an antireflection layer onto the antiglare layer, and drying and curing the resulting coating film. The coating liquid for forming an antireflection layer may contain, for example, a resin component (curable compound), a fluorine-containing additive, hollow particles, solid particles, a solvent, and the like, and can be obtained, for example, by mixing these.

[0045] The curing mechanism of the resin component (curable compound) contained in the coating liquid for forming the antireflection layer can be, for example, a thermosetting type or a photocurable type. For example, a curable compound having at least one of an acrylate group and a methacrylate group is used as the resin component, and examples thereof include oligomers or prepolymers such as acrylates and methacrylates of polyfunctional compounds such as silicone resins, polyester resins, polyether resins, epoxy resins, urethane resins, alkyd resins, spiroacetal resins, polybutadiene resins, polythiolpolyene resins, and polyhydric alcohols. These may be used alone or in combination of two or more types.

[0046] The resin component may be, for example, a reactive diluent having at least one of an acrylate group and a methacrylate group. The reactive diluent may be, for example, a reactive diluent described in JP-A-2008-88309, and may include, for example, a monofunctional acrylate, a monofunctional methacrylate, a polyfunctional acrylate, and a polyfunctional methacrylate. From the viewpoint of obtaining excellent hardness, trifunctional or higher acrylates and trifunctional or higher methacrylates are preferably used as the reactive diluent. Examples of the reactive diluent include butanediol glycerin ether diacrylate, acrylate of isocyanuric acid, and methacrylate of isocyanuric acid. These may be used alone or in combination of two or more. For example, a curing agent may be used to harden the resin component. For example, a known polymerization initiator (for example, a thermal polymerization initiator, a photopolymerization initiator, etc.) may be used as the curing agent.

[0047] The fluorine-containing additive may be, for example, an organic compound containing fluorine, or an inorganic compound containing fluorine. Examples of the organic compound containing fluorine include a fluorine-containing antifouling coating agent, a fluorine-containing acrylic compound, and a fluorine-silicon-containing acrylic compound. A commercially available product may be used as the organic compound containing fluorine. Specific examples of the commercially available product include "KY-1203" manufactured by Shin-Etsu Chemical Co., Ltd. and "Megafac" manufactured by DIC Corporation. The content of the fluorine-containing additive may be, for example, 0.05 parts by weight or more, 0.1 parts by weight or more, 0.15 parts by weight or more, 0.20 parts by weight or more, or 0.25 parts by weight or more, and may be 20 parts by weight or less, 15 parts by weight or less, 10 parts by weight or less, 5 parts by weight or less, or 3 parts by weight or less, relative to 100 parts by weight of the resin component.

[0048] As the hollow particles, for example, silica particles, acrylic particles, and acrylic-styrene copolymer particles are used. As the hollow silica particles, commercially available products (for example, trade names "Suluria 5320" and "Suluria 4320" manufactured by JGC Catalysts and Chemicals Co., Ltd.) can be used. The weight average particle diameter of the hollow particles may be, for example, 30 nm or more, 40 nm or more, 50 nm or more, 60 nm or more, or 70 nm or more, and may be 150 nm or less, 140 nm or less, 130 nm or less, 120 nm or less, or 110 nm or less. The shape of the hollow particles is not particularly limited, but is preferably approximately spherical. Specifically, the aspect ratio of the hollow particles is preferably 1.5 or less. The content of the hollow particles may be, for example, 30 parts by weight or more, 50 parts by weight or more, 70 parts by weight or more, 90 parts by weight or more, or 100 parts by weight or more, and may be 300 parts by weight or less, 270 parts by weight or less, 250 parts by weight or less, 200 parts by weight or less, or 180 parts by weight or less, relative to 100 parts by weight of the resin component.

[0049] As the solid particles, for example, silica particles, zirconia particles, and titania particles are used. As the solid silica particles, commercially available products (for example, trade names "MEK-2140Z-AC", "MIBK-ST", and "IPA-ST" manufactured by Nissan Chemical Industries, Ltd.) can be used. The weight average particle diameter of the solid particles may be, for example, 5 nm or more, 10 nm or more, 15 nm or more, 20 nm or more, or 25 nm or more, and may be 330 nm or less, 250 nm or less, 200 nm or less, 150 nm or less, or 100 nm or less. The shape of the hollow particles is not particularly limited, but is preferably approximately spherical. Specifically, the aspect ratio of the hollow particles is preferably 1.5 or less. The content of the solid particles may be, for example, 5 parts by weight or more, 10 parts by weight or more, 15 parts by weight or more, 20 parts by weight or more, or 25 parts by weight or more, and may be 150 parts by weight or less, 120 parts by weight or less, 100 parts by weight or less, or 80 parts by weight or less, relative to 100 parts by weight of the resin component.

[0050] Any suitable solvent may be used as the solvent. Examples of the solvent include alcohols such as methanol, ethanol, isopropyl alcohol, butanol, TBA (tertiary butyl alcohol), and 2-methoxyethanol; ketones such as acetone, methyl ethyl ketone, MIBK (methyl isobutyl ketone), and cyclopentanone; esters such as methyl acetate, ethyl acetate, butyl acetate, and PMA (propylene glycol monomethyl ether acetate); ethers such as diisopropyl ether and propylene glycol monomethyl ether; glycols such as ethylene glycol and propylene glycol; cellosolves such as ethyl cellosolve and butyl cellosolve; aliphatic hydrocarbons such as hexane, heptane, and octane; and aromatic hydrocarbons such as benzene, toluene, and xylene. These may be used alone or in combination of two or more. The content of the solvent may be, for example, such that the weight of the solids relative to the total weight of the coating liquid for forming the antireflection layer is, for example, 0.1 wt % or more, 0.3 wt % or more, 0.5 wt % or more, 1.0 wt % or more, or 1.5 wt % or more, or 20 wt % or less, 15 wt % or less, 10 wt % or less, 5 wt % or less, or 3 wt % or less.

[0051] The coating liquid for forming the antireflection layer can be applied by known coating methods such as fountain coating, die coating, spin coating, spray coating, gravure coating, roll coating, and bar coating. The drying temperature for the coating is, for example, 30°C to 200°C, and the drying time is, for example, 30 seconds to 90 seconds. The coating can be cured by, for example, heating or light irradiation (typically, ultraviolet irradiation). A high-pressure mercury lamp, for example, is used as a light source for light irradiation. The dose of ultraviolet irradiation is 50 mJ / cm as the integrated exposure dose at an ultraviolet wavelength of 365 nm. 2 ~500mJ / cm 2 It is preferable that:

[0052] Preferably, the surface treatment layer may have antifouling properties. Specifically, the surface treatment layer may contain at least one of fluorine and silicon. On the other hand, such a surface treatment layer may reduce adhesion to the protective film. According to an embodiment of the present invention, even for such a surface treatment layer (laminated film), a laminate with excellent adhesion can be obtained by surface-modifying a predetermined protective film, and a polarizing plate with excellent appearance can be provided.

[0053] The thickness of the surface treatment layer is, for example, 1 μm to 20 μm, preferably 2 μm to 15 μm, and more preferably 3 μm to 10 μm.

[0054] The contact angle of the surface of the surface treatment layer (laminated film) is, for example, from 90° to 125°, and the surface roughness Ra of the laminated film (surface treatment layer) is, for example, from 0.01 μm to 0.3 μm. EXAMPLES

[0055] The present invention will be specifically described below with reference to examples, but the present invention is not limited to these examples. The thickness, surface roughness Ra, and reflectance are values ​​measured by the following measurement methods. Furthermore, unless otherwise specified, "parts" and "%" in the examples and comparative examples are based on weight. <Thickness> The thickness of 10 μm or less was measured using a scanning electron microscope (manufactured by JEOL, product name "JSM-7100F"), and the thickness of more than 10 μm was measured using a digital micrometer (manufactured by Anritsu, product name "KC-351C"). <Surface roughness Ra> The arithmetic mean surface roughness Ra (μm) was measured according to JIS B 0601 (1994 edition). Specifically, the measurement target was attached to a glass plate (MICRO SLIDE GLASS, manufactured by MATSUNAMI Co., Ltd., product number S, thickness 1.3 mm, 45 mm x 50 mm) with an adhesive to prepare a measurement sample. Next, using a stylus-type surface roughness measuring instrument (High-precision fine shape measuring instrument, product name "Surfcorder ET4000", manufactured by Kosaka Laboratory Co., Ltd.) with a measuring needle with a curvature radius R of 2 μm at the tip (diamond), the uneven shape of the outermost surface of the obtained measurement sample was measured in a certain direction under the conditions of a scanning speed of 1 mm / sec, a cutoff value of 0.8 mm, and a measurement length of 12 mm. Based on this measurement, the arithmetic mean surface roughness Ra was calculated. The high-precision fine shape measuring instrument automatically calculates the measurement value. <Reflectance> Measurements were made using an ultraviolet-visible-infrared spectrophotometer (Hitachi High-Tech Science, product name "U-4100") To measure the reflectance of the surface treatment layer side of the laminated film, the laminated film was attached to a black acrylic plate with an adhesive to prepare a measurement sample. <Contact angle> The water contact angle of the surface treatment layer side of the laminated film was measured. Specifically, the measurement was performed by the sessile drop method using a contact angle meter (manufactured by Kyowa Interface Science Co., Ltd., product name "DMo-501 type", control box "DMC-2", control and analysis software "FAMAS (version 5.0.30)") in an environment of 23°C and 50% RH. The amount of distilled water dropped was 2 μL, and the contact angle was calculated by the θ / 2 method from the image taken 5 seconds after the drop.

[0056] [Example 1] (Preparation of polarizer) A long roll of a 30 μm-thick polyvinyl alcohol (PVA) resin film (manufactured by Kuraray, product name "PE3000") was uniaxially stretched in the longitudinal direction to 5.9 times its original size using a roll stretching machine while simultaneously undergoing swelling, dyeing, crosslinking, and washing treatments in that order, and finally a drying treatment to produce a 12 μm-thick polarizer. The above swelling treatment was performed by stretching the film 2.2 times while treating with pure water at 20°C. Next, the dyeing treatment was performed by stretching the film 1.4 times while treating in an aqueous solution at 30°C in which the weight ratio of iodine to potassium iodide was 1:7, with the iodine concentration adjusted so that the single transmittance of the resulting polarizer was 45.0%. Next, the crosslinking treatment was performed in two stages, and the first stage was stretched 1.2 times while treating in an aqueous solution at 40°C in which boric acid and potassium iodide were dissolved. The aqueous solution in the first stage crosslinking treatment had a boric acid content of 5.0% by weight and a potassium iodide content of 3.0% by weight. The second stage crosslinking treatment was performed by stretching the film 1.6 times while treating in an aqueous solution at 65°C in which boric acid and potassium iodide were dissolved. The aqueous solution in the second stage crosslinking treatment had a boric acid content of 4.3% by weight and a potassium iodide content of 5.0% by weight. Next, the film was washed with an aqueous potassium iodide solution at 20° C. The aqueous solution used for the washing treatment had a potassium iodide content of 2.6% by weight. Finally, the film was dried at 70° C. for 5 minutes to obtain a polarizer.

[0057] (Preparation of Laminate A) A TAC film having a thickness of 25 μm was attached to one side of the obtained polarizer via an ultraviolet-curable adhesive, thereby obtaining a laminate A.

[0058] (Preparation of Laminate B) The adhesive surface of a polyethylene protective film (Toray Film Processing Co., Ltd., "Tretec (registered trademark) 7832C", thickness: 50 μm, adhesive surface Ra: 0.23 μm) was subjected to corona treatment with a strength of 24 W·min / m 2 After subjecting the protective film to corona treatment under the above conditions, the adhesive surface was attached to the surface treatment layer side of a TAC film (thickness 32 μm) on which a surface treatment layer was formed, to obtain a laminate B. The TAC film on which a surface treatment layer was formed was a film in which a surface treatment layer (thickness: 7 μm, reflectance: 1.4%, Ra: 0.06 μm, contact angle: 100°) was formed on a TAC film (thickness 25 μm), and the surface treatment layer was formed by the procedure shown below. The Ra of the adhesive surface of the protective film after corona treatment was 0.03 μm.

[0059] (Formation of surface treatment layer) 1. Formation of anti-glare layer A mixture of 50 parts by weight of an ultraviolet-curable urethane acrylate resin (manufactured by Nippon Synthetic Chemical Industry Co., Ltd., product name "UV1700TL", solid content 80%) and 50 parts by weight of a multifunctional acrylate containing pentaerythritol triacrylate as the main component (manufactured by Osaka Organic Chemical Industry Co., Ltd., product name "Viscoat #300", solid content 100%) was prepared. For 100 parts by weight of the resin solid content of the mixture, 4 parts by weight of crosslinked polymethylmethacrylate particles (manufactured by Sekisui Chemical Co., Ltd., trade name "Techpolymer", weight average particle size: 3 μm, refractive index: 1.525), 1.5 parts by weight of synthetic smectite (manufactured by Co-op Chemical Co., Ltd., trade name "Lucentite SAN") which is an organoclay (thixotropy imparting agent), 3 parts by weight of photopolymerization initiator (manufactured by BASF, trade name "OMNIRAD907"), and 0.15 parts by weight of leveling agent (manufactured by Kyoeisha Chemical Co., Ltd., trade name "LE303", solid content 40%) were mixed. Here, the organoclay was used after diluting with toluene to a solid content of 6%. The obtained mixture was diluted with a mixed solvent of toluene / ethyl acetate / cyclopentanone (CPN) (weight ratio 35 / 41 / 24) so ​​that the solid content concentration was 40% by weight, to prepare an antiglare layer-forming material (coating liquid).

[0060] The obtained antiglare layer-forming material (coating liquid) was applied onto a TAC film (thickness 25 μm, Fujifilm Corporation, product name "TJ25UL"), after which ultraviolet light having a wavelength of 365 nm was applied from a high-pressure mercury lamp at an integrated light quantity of 300 mJ / cm. 2 The coating film was irradiated so as to obtain a coating thickness of 7 μm, and then dried by heating at 80° C. for 60 seconds.

[0061] 2. Formation of anti-reflection layer 100 parts by weight of a polyfunctional acrylate having pentaerythritol triacrylate as a main component (manufactured by Osaka Organic Chemical Industry Co., Ltd., trade name "Viscoat #300", solid content 100% by weight), 100 parts by weight of hollow nanosilica particles (manufactured by JGC Catalysts and Chemicals Co., Ltd., trade name "Surulia 5320", solid content 20% by weight, weight average particle diameter 75 nm), 100 parts by weight of solid nanosilica particles (manufactured by Nissan Chemical Industries, Ltd., trade name "MEK-2140Z-AC", solid content 30% by weight, weight average particle diameter 10 nm), 12 parts by weight of a fluorine-containing additive (manufactured by Shin-Etsu Chemical Co., Ltd., trade name "KY-1203", solid content 20% by weight), and 3 parts by weight of a photopolymerization initiator (manufactured by BASF, trade name "OMNIRAD907", solid content 100% by weight) were mixed. To the mixture, a mixed solvent of TBA, MIBK and PMA in a weight ratio of 60:25:15 was added so that the total solid content was 4% by weight, and the mixture was stirred to prepare a coating liquid for forming an antireflection layer.

[0062] The obtained coating liquid for forming an anti-reflection layer was applied onto the anti-glare layer using a wire bar. The applied coating liquid was heated at 80°C for 1 minute and dried to form a coating film. The obtained coating film was irradiated with an integrated light quantity of 300 mJ / cm2 from a high-pressure mercury lamp. 2 The coating was then cured by irradiating it with ultraviolet light of 1000 ohms to form an anti-reflection layer having a thickness of 0.1 μm. In this way, a surface treatment layer was formed.

[0063] (Preparation of polarizing plate) A polarizing plate was obtained by bonding laminate A and laminate B with an ultraviolet-curable adhesive so that the polarizer of laminate A and the TAC film of laminate B faced each other. When bonding laminate A and laminate B, laminate A and laminate B were sandwiched between a pair of pressure members and pressed at 0.3 MPa. The above lamination was performed while the substrates were being transported by rolls.

[0064] [Example 2] The corona treatment intensity of the protective film is 36 W·min / m 2 A polarizing plate was obtained in the same manner as in Example 1 except for the above.

[0065] [Example 3] The corona treatment intensity of the protective film is 48 W·min / m 2 A polarizing plate was obtained in the same manner as in Example 1 except for the above.

[0066] [Comparative Example 1] A polarizing plate was obtained in the same manner as in Example 1, except that the protective film was not subjected to the corona treatment.

[0067] [Comparative Example 2] A polarizing plate was obtained in the same manner as in Example 1, except that a polyethylene-based protective film (manufactured by Toray Film Processing Co., Ltd., "Tretec (registered trademark) R304C", thickness: 30 μm, Ra of adhesive surface: 0.72 μm) was used as the protective film, and that the protective film was not subjected to corona treatment.

[0068] The following evaluations were carried out for the Examples and Comparative Examples. The evaluation results are summarized in Table 1. <Evaluation> 1. Adhesion A sample cut out from the obtained laminate B to a size of 50 mm in width and 100 mm in length was peeled in the length direction at a peel speed of 300 mm / min and a peel angle of 180° using a universal tensile tester, and the peel force (N / 50 mm) was measured. Specifically, the peel force of the protective film against the surface treatment layer was measured. The measurement was performed in an environment of 23°C and 50% RH. 2.Appearance The appearance of the obtained polarizing plate was visually observed and evaluated by checking for the occurrence of unevenness. Specifically, in each Example and Comparative Example, two polarizing plates were prepared, and these were left to stand for 120 hours under an environment of 60°C and 90% RH, and then stacked so that the absorption axes of the polarizers were perpendicular to each other, and this state was observed on a backlight. 3. Transportability The transportability of the film was evaluated until a polarizing plate was obtained.

[0069] [Table 1]

[0070] In the examples, excellent adhesion was obtained. In Example 3, the protective film was wavy due to the corona treatment, which caused roll transport failure, and the TAC film on which the surface treatment layer was formed could not be laminated well, and the adhesion could not be evaluated. As shown in FIG. 2A, no unevenness was observed in the example, and an excellent appearance was obtained, whereas in Comparative Example 2, unevenness (spots) was observed, as shown in FIG. 2B. [Industrial Applicability]

[0071] The polarizing plate obtained by the embodiment of the present invention can be suitably used as a polarizing plate for an image display device, representative examples of which include a liquid crystal display device, an organic EL display device, and an inorganic EL display device. [Explanation of symbols]

[0072] 10 Protective film 20 Laminated Film 21 Base material (protective layer) 22 Surface treatment layer 30 Polarizer 40 protective layer 100 Polarizing Plate

Claims

1. A protective film having a first main surface and a second main surface opposed to each other, the first main surface having a surface roughness Ra of 0.5 μm or less, and surface-modifying the first main surface; Obtaining a laminate by bonding the surface-modified surface of the protective film to the surface-treated layer of a laminate film having a substrate and a surface-treated layer; and laminating a polarizer on the substrate side of the laminate; the surface treatment of the surface treatment layer is selected from a hard coat treatment, an anti-reflection treatment, an anti-sticking treatment, an anti-glare treatment, and an anti-fouling treatment, and the contact angle of the surface of the surface treatment layer is 90° or more and 125° or less; The surface modification is performed by at least one of a corona treatment or a plasma treatment, and the surface roughness Ra of the first main surface is reduced by 0.1 μm to 0.4 μm by the surface modification. A method for manufacturing a polarizing plate.

2. The method according to claim 1 , wherein the first main surface has a surface roughness Ra of 0.15 μm or less after the surface modification.

3. The surface modification is performed by the corona treatment, and the treatment intensity of the corona treatment is 10 W min / m 2 Above, 50W・min / m 2 The method according to claim 1 or 2, wherein:

4. The method according to claim 1 , further comprising the steps of: overlapping the laminate and the polarizer; and sandwiching and pressing the laminate and the polarizer between a pair of pressing members.

5. The method according to claim 1 , wherein the protective film is a polyolefin film.

6. The method according to claim 1 , wherein the surface treatment layer contains at least one of fluorine and silicon.

7. The method according to claim 1 , wherein the reflectance of the surface treatment layer side of the laminated film is 3% or less.

Citation Information

Patent Citations

  • Method of manufacturing polarizing plate, polarizing plate and image display device

    JP2008089725A

  • Method for manufacturing polarizing plate, polarizing plate, and liquid crystal display device

    JP2009139510A

  • Method of manufacturing polarizing plate with surface treated layer

    JP2009237489A

  • Optical laminate with surface protective film

    JP2019133049A

  • Retardation film and optical device using the same

    JP3325560B2